2016
DOI: 10.1073/pnas.1613855114
|View full text |Cite
|
Sign up to set email alerts
|

Matrix stiffening promotes a tumor vasculature phenotype

Abstract: Tumor microvasculature tends to be malformed, more permeable, and more tortuous than vessels in healthy tissue, effects that have been largely attributed to up-regulated VEGF expression. However, tumor tissue tends to stiffen during solid tumor progression, and tissue stiffness is known to alter cell behaviors including proliferation, migration, and cell-cell adhesion, which are all requisite for angiogenesis. Using in vitro, in vivo, and ex ovo models, we investigated the effects of matrix stiffness on vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
338
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 335 publications
(352 citation statements)
references
References 59 publications
14
338
0
Order By: Relevance
“…Accordingly, we observed a lower QPOL signal in tumor sections from mice treated with BAPN compared to the untreated control (Figure E). These results are consistent with the reduced stiffness and contractility of tumor tissue observed in BAPN treated mice . Of particular relevance, the quantification of the retardance revealed that we could distinguish between soft and stiff tumors (Figure F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we observed a lower QPOL signal in tumor sections from mice treated with BAPN compared to the untreated control (Figure E). These results are consistent with the reduced stiffness and contractility of tumor tissue observed in BAPN treated mice . Of particular relevance, the quantification of the retardance revealed that we could distinguish between soft and stiff tumors (Figure F).…”
Section: Resultsmentioning
confidence: 99%
“…Type I collagen was isolated from rat‐tail tendons and extracted in 0.1% sterile acetic acid at 4°C as described previously . Stiffness of the collagen scaffolds was controlled either by changing the collagen density or by increasing collagen crosslinking through non‐enzymatic glycation.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the ratio of acrylamide (40% w/v; Bio-Rad, Hercules, CA) and bis-acrylamide (2% w/v; Bio-Rad) was varied to tune gel stiffness from 1 to 10 kPa to mimic vascular and tumorous tissue as described previously [22,26,39]. Gels were coated with either 0.1 mg/ml collagen type I (BD Biosciences, San Jose, CA) or fibronectin (Thermo Fisher Scientific, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Enhanced ECM density and rigidity facilitates liver and breast cancer detection via , and may indicate risk factors for tumour progression and therapeutic response 53,54 . ECM changes alter mechanotransduction 55,56 and promote malignant behaviour by disrupting epithelial morphogenesis 57 , growth factor secretion and signalling 58 , invasive phenotype 59,60 and stem cell differentiation 61 , as well as angiogenesis and vessel permeability 62 . As such, efforts have focused on characterizing altered ECM and how it contributes to tumour progression, with the goal of normalizing ECM for therapy 3,63 (FIG.…”
Section: Physical Microenvironment Of the Tumourmentioning
confidence: 99%